Damaged Keratin Filament Network Caused by KRT5 Mutations in Localized Recessive Epidermolysis Bullosa Simplex - Chen, Fuying; Yao, Lei; Zhang, Xue; Gu, Yan; Yu, Hong; Yao, Zhirong; Zhang, Jia; Li, Ming (Frontiers in Genetics, 2021)
Epidermolysis bullosa simplex (EBS) is a blistering dermatosis that is mostly caused by dominant mutations in KRT5 and KRT14. In this study, we investigated one patient with localized recessive EBS caused by novel homozygous c.1474T>C mutations in KRT5. Biochemical experiments showed a mutation-induced alteration in the keratin 5 structure, intraepidermal blisters, and collapsed keratin intermediate filaments, though no quantitative change at the protein levels and interaction between keratin 5 and keratin 14. Moreover, we found that MAPK signalling was inhibited, while desmosomal protein desmoglein 1 (DSG1) was upregulated upon KRT5 mutation. Inhibition of EGFR phosphorylation upregulated DSG1 levels in an in vitro model. Collectively, our findings suggest that this mutation leads to localized recessive EBS and that keratin 5 is involved in maintaining DSG1 via activating MAPK signalling.